Challenges of Inclusive Elections: Obstacles and Efforts to Protect the Voting Rights of the Meratus Dayak Indigenous Community - Muhammad Al Ghifari; Pradana, Galang Bayu; Paragaye, Yuan Laorens (International Journal of Integrative Sciences, 2024)
Inclusive elections are the foundation of democracy that prioritizes the participation of all citizens, including indigenous peoples. This paper explores the challenges faced by the Dayak Meratus indigenous people, such as low literacy, limited access to information, geographical barriers, and minimal political representation, which hinder their participation in elections. Using a qualitative descriptive method based on literature studies, this study finds that these obstacles can be overcome through a local wisdom-based approach, strengthening communication infrastructure, and cross-sector collaboration between the government, NGOs, and indigenous communities. This approach not only increases political awareness but also guarantees the voting rights of indigenous peoples, thus creating inclusive and fair elections. This paper highlights the importance of adaptive strategies to ensure democracy is accessible to all elements of society, especially those in remote areas with limited education and information